Potensi Konflik Kepentingan dalam Pendirian Badan Hukum Perorangan Pasca Revisi Undang-Undang Perseroan Terbatas dalam Omnibus Law - Febri Jaya (Kosmik Hukum, 2021)
The need for employment in Indonesia continues to increase every year, so there is naturally a concern that there will be conditions where the need for employment is more than the available employment opportunities. Therefore, several actions have been taken by the executive and legislature to anticipate these conditions, one of which is by facilitating the establishment of a limited liability company which previously had to be established by 2 (two) or more people to only 1 (one) person with certain conditions regulated in Law Number 11 of 2020 concerning Job Creation. In practice, there are many internal disputes related to conflicts of interest in a limited liability company established by 2 (two) or more people, even though when it is founded by 2 (two) or more people, supervision of the management of a limited liability company will certainly be better than that of a limited liability company established. by 1 (one) person. This study discusses the potential for a conflict of interest in a limited liability company established by 1 (one) person who also serves as the only member of the Director in the company.Keywords: Limited Liability Company, Conflict of Interest, Job Creation.